ANALISIS KAPASITAS TANGKI SEPTIK KOMUNAL DESA SUNGAI BAUNG KECAMATAN TALANG UBI PALI - Agus Muslim; Kiagus Muhammad Aminuddin; David Bahrin; Deby Ansyory (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2026)
The Community-Based Sanitation Program (SANIMAS) is a component of the Urban Sanitation and Rural Infrastructure (USRI) program that aims to create and improve the quality of life of the community, both individually and in groups, especially low-income communities in densely populated, slum and sanitation-prone urban areas. This study focuses on calculating the capacity and calculating the budget for the construction of a communal septic tank (RAB). The research location is in Sungai Baung Village, Talang Ubi District, PALI Regency. The design of the Communal Septic Tank (IPAL) building with an emptying time of 2 years. The population increase of 1.6% in 5 years resulted in a total of 355 communal septic tank users P (2020). From the calculation results, it was obtained that the IPAL built had a tank volume of 61 m3/day with a waste volume of 28.4 m3/day where the required sludge tank capacity was 28.5 m3 with a minimum capacity requirement in one day of 1,434 liters/person/day and a water capacity requirement of 5.1 m3.